Specific IgG4: Possible Role in the Pathogenesis and a New Marker in the Diagnosis of Anisakis‐associated Allergic Disease. (February 2014) - Daschner, A.; Fernández‐Fígares, V.; Rodero, M.; Valls, A.; De Frutos, C.; Ubeira, F. M.; Cuéllar, C.
Abstract IgG4 and IgE are immunoglobulin isotypes which are mediated by the same Th2‐mediated mechanism. The postulated pathogenic and protective function of IgE or IgG4, respectively, in allergic disease is opposite in parasitic infection. The possible role of IgG4 against recombinant major allergens on the appearance of different forms of Anisakis simplex‐associated allergic disease was studied. Gastro‐allergic anisakiasis (GAA) and Anisakis‐sensitization‐associated chronic urticaria (CU+) were compared for specific IgE, IgG4 and the respective recognition of Ani s 1 and Ani s 7. Gastro‐allergic anisakiasis showed higher IgE and IgG4 levels against crude extract and both recombinant allergens. Whereas IgE recognition of Ani s 7 did not differ and supports both clinical entities to be associated with previous acute parasitism, the IgE recognition rates of Ani s 1 and IgG4 recognition of both Ani s 1 and Ani s 7 were higher in GAA. IgG4 levels were associated with IgE, but also with age, time to last parasitic episode and frequency of fish intake. Logistic regression analysis showed that the presence of specific IgG4 against Ani s 7 was an independent marker associated with GAA. In the diagnosis of Anisakis‐associated allergic disease phenotypes (GAA versus CU+), measurement of specific IgG4 against recombinant allergens could be useful. Further, evaluation of specific IgE and IgG4 facilitates more insight into the protective versus pathogenic potential of IgE and IgG4.